1996
DOI: 10.1111/j.1476-5381.1996.tb15483.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium antagonists on endothelin‐1‐induced myocardial ischaemia and oedema in the rat

Abstract: 1 The effects of the calcium channel blockers, verapamil and nifedipine on myocardial ischaemia and oedema evoked by endothelin-l (ET-1) or IRL 1620, an ETB receptor-selective agonist were studied in anaesthetized and conscious rats. 2 Bolus injection of ET-1 (1 nmol kg-', i.v.) or IRL 1620 (1 nmol kg-', i.v.) to conscious chronically catheterized rats evoked a transient depressor response followed by a prolonged pressor effect. Corresponding to changes in blood pressure, a transient tachycardia and a sustaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…In coronary veins, where constrictor ET Breceptors are the sole ET-receptor subtype present on smooth muscle cells, vasoconstriction due to increased ET-1 will be unopposed by ET A -receptor antagonism. In addition, stimulation of vasoconstrictor ET B -receptors on cardiac veins might also take part in the development of cardiac edema by increasing postcapillary resistance and capillary filtration pressure (Filep et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In coronary veins, where constrictor ET Breceptors are the sole ET-receptor subtype present on smooth muscle cells, vasoconstriction due to increased ET-1 will be unopposed by ET A -receptor antagonism. In addition, stimulation of vasoconstrictor ET B -receptors on cardiac veins might also take part in the development of cardiac edema by increasing postcapillary resistance and capillary filtration pressure (Filep et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…After ischemia/reperfusion the number of patent capillaries is increased by treatment with the ET A -receptor antagonist BQ-123 (Maxwell et al 2000), and myocardial thickening is significantly decreased by the ET A -receptor antagonist LU 135252 (Galiuto 2000). While cardiac edema can be provoked by ET A as well as ET B -receptor agonists (Filep et al 1996), non-specific blockade of both ET-receptor subtypes during endotoxin shock is no more effective than isolated ET A -receptor antagonism in preventing albumin extravasation (Filep 2000). These observations were explained by actions of ET-1 on coronary smooth muscle cells, cardiomyocytes, and polymorphonuclear leukocytes, all of which are known to bind ET-receptor antagonists, but the pathophysiological mechanisms, however, remain unclear partly because of lack of information about ET-receptor subtype distribution in the coronary microcirculation.…”
Section: Introductionmentioning
confidence: 96%
“…RAAS blocking agents thus might influence ET-1 plasma concentrations independent of the actual blood pressure. It was likewise shown that also beta blockers [29, 30] and calcium channel blockers [31-32] alter the paracrine ET-1 system. The majority of the remaining studies reported plasma ET-1 concentrations in treatment naive hypertensive patients, see table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin has recently been recognized as one of the key mediators of myocardial ischemia (13). Elevated plasma concentrations of endothelin can be detected in patients exhibiting coronary spasm (14).…”
Section: Discussionmentioning
confidence: 99%